Pharmacological Improvement of Oncolytic Virotherapy - Selman, Mohammed (Université d'Ottawa / University of Ottawa, 2018)
Oncolytic viruses (OV) are an emerging class of anticancer bio-therapeutics that induce antitumor immunity through selective replication in cancer cells. However, the efficacy of OVs as single agents remains limited. We postulate that resistance to oncolytic virotherapy results in part from the failure of tumor cells to be sufficiently infected. In this study, we provide evidence that in the context of sarcoma, a highly heterogeneous malignancy, the infection of tumors by different oncolytic viruses varies greatly. Similarly, for a given oncolytic virus, productive infection of tumors across patient samples varies by many orders of magnitude. To overcome this issue, we hypothesize that the infection of resistant tumors can be achieved through the use of selected small molecules. Here, we have identified two novel drug classes with the ability to improve the efficacy of OV therapy: fumaric and maleic acid esters (FMAEs) and vanadium compounds. FMAEs are enhancing infection of cancer cells by several oncolytic viruses in cancer cell lines and human tumor biopsies. The ability of FMAEs to enhance viral spread is due to their ability to inhibit type I IFN production and response, which is associated with their ability to block nuclear translocation of transcription factor NF-κB. Vanadium-based phosphatase inhibitors enhance OV infection of RNA viruses in vitro and ex vivo, in resistant cancer cell lines. Mechanistically, this involves subverting the antiviral type I IFN response towards a death-inducing and proinflammatory type II IFN response, leading to improved OV spread, increased bystander killing of cancer cells, and enhanced anti-tumor immune-stimulation. Both FMAEs and vanadium compounds improve therapeutic outcomes of OV treatment in syngeneic tumor models, leading to durable responses, even in models otherwise refractory to OV and drug alone. Overall, we showcased novel avenues for the development of improved immunotherapy strategies.
Keywords: Oncolytic virus; Vanadate; Dimethyl fumarate; Sarcoma